A phenomenological note: black religion as Christian conjuration - Smith, Theophus H. (The Journal of the Interdenominational Theological Center, 1983)
Taking a phenomenological approach, this article indicates how the black religious experience in the United States has both retained and transformed the conjurational mode of African spirituality. Examination of the following texts shows different ways in which the phenomenon operates as a genuine Afro-Christian synthesis: W E B DuBois's (1868-1963) autobiographical, poetic and prose writing; the 1829 freedom pamphlets (Ethiopian) of David Walker and Robert Alexander Young; and a Harlem Renaissance poem by Countee Cullen ("Heritage," 1925). A socio-linguistic theory of biculturality (Marks, Blauner, DuBois), in combination with previous scholarship in the history and phenomenology of spirit possession (Wilmore, Mitchell) provide a theoretical framework supporting the conclusion: there is no intrinsic basis for excluding a spirituality of conjuration from Christian theology.
Keywords: Africa – Religion; African Americans – Religion; Blacks – Religion; Culture and religion; Du Bois; W E B. (William Edward Burghardt); 1868-1963; Freedom – Religious aspects; Holy Spirit; Spirit possession; Spirituality